The entrepreneurial mind-set of university students: a cross-cultural comparison between Namibia and Germany. (1st January 2011) - Haase, Heiko; Lautenschläger, Arndt; Rena, Ravinder
The objective of this article is to set a cornerstone to compare and understand the phenomenon of graduate entrepreneurship in developing and developed countries. Our central research questions are: Are there differences in the entrepreneurial intentions of university students? What are the factors that might explain potential differences in their entrepreneurial mind-set? In response to these questions, we performed a cross-sectional study exploring the prospective career paths of 2, 353 university students from Namibia as well as from Eastern and Western Germany. We found that Namibian students have a higher entrepreneurial intention compared to their German counterparts. We detected several differences between both countries and revealed explanatory factors. However, they are not sufficient to explain the 'regional dimension' of the higher entrepreneurial intentions in Namibia. Several implications are presented.